Desenvolvimento e validação de metodologia para avaliação de rupatadina por cromatografia líquida e eletroforese capilar - Nogueira, Daniele Rubert (2009)
Rupatadine is a second generation antihistamine H1, from the pyperidinic group, which inhibits both the histamine and platelet activating factor effects, and is clinically used for the treatment of allergic rhinitis and chronic urticaria. The methods for the evaluation of rupatadine in pharmaceutical products were developed and validated in the present work. The reversed-phase liquid chromatography (RP-LC) analysis was carried out using a Gemini C18 column (150 mm x 4.6 mm), maintained at 30 oC. The mobile phase consisted of ammonium acetate buffer 0.01 M, pH 3.0 with 0.05% of 1-heptanosulfonic acid/acetonitrile (71.5:28.5 v/v), run at a flow rate of 1.0 mL/min with detection at 242 nm. The chromatographic separation was obtained within 7 min and it was linear in the concentration range of 0.5-400 μg/mL (r2=0.9999). The capillary electrophoresis method was developed and validated, using the micellar electrokinetic chromatography (MEKC) as the separation mode, and nimesulide as internal standard (IS). The analysis were performed on a fused-silica capillary (50 μm id, effective length, 40 cm), maintained at 35ºC, using electrolyte solution consisted of 15 mM borate buffer and 25 mM anionic detergent SDS solution at pH 10, with detection by photodiode array detector set at 205 nm. The injection was performed using the hydrodynamic mode at 50 mbar for 5 s, and a constant voltage of 25 kV was applied during the analysis. The electrophoretic separation was obtained within 6 min and it was linear in the oncentration range of 0.5-150 μg/mL (r2=0.9996). The procedures were validated evaluating parameters such as the specificity, linearity, precision, accuracy, limits of detection and quantitation, robustness, and system suitability test, giving results within the acceptable range. The proposed methods were applied for the analysis of pharmaceutical products, showing significant correlation (P>0.05) of the results. Therefore, the procedures can be applied to improve the quality control of pharmaceutical products and to assure the safety and therapeutic efficacy of the drug.